Direct and Indirect Effects of Fibroblast Growth Factor (FGF) 15 and FGF19 on Liver Fibrosis Development. Issue 2 (9th August 2019) - Schumacher, Justin D.; Kong, Bo; Wu, Jason; Rizzolo, Daniel; Armstrong, Laura E.; Chow, Monica D.; Goedken, Michael; Lee, Yi‐Horng; Guo, Grace L.
Abstract : Farnesoid X receptor (FXR) induces fibroblast growth factor 15 (FGF15; human ortholog FGF19) in the gut to potently inhibit bile acid (BA) synthesis in the liver. FXR activation in hepatic stellate cells (HSCs) reduces liver fibrosis (LF). Fgf15 –/– mice develop attenuated LF, but the underlying mechanisms for this protection are unclear. We hypothesized that FGF15/19 functions as a profibrotic mediator or mitogen to HSCs and increased BAs in Fgf15 –/– mice leads to enhanced FXR activation in HSCs, subsequently reducing fibrogenesis. In this study, complimentary in vivo and in vitro approaches were used: (1) CCl4 ‐induced LF model in wild type (WT), Fgf15 –/–, and Fgf15 transgenic (TG) mice with BA levels modulated by feeding cholestyramine‐ or cholic acid–containing diets; (2) analysis of primary HSCs isolated from WT and Fgf15 –/– mice; and (3) treatment of a human HSC line, LX‐2, with FXR activators and/or recombinant FGF19 protein. The results showed that Fgf15 –/– mice had lower basal collagen expression, which was increased by BA sequestration. CCl4 induced fibrosis with similar severity in all genotypes; however, cholestyramine increased fibrosis severity only in Fgf15 –/– mice. HSCs from Fgf15 –/– mice showed increased FXR activity and reduced expression of profibrotic mediators. In LX‐2 cells, FXR activation increased peroxisome proliferator‐activated receptor gamma activity and reduced proliferation. FGF19 activated both signal transducer and activator of transcription 3 and c‐Jun N‐terminal kinase pathways and reduced nuclear factor kappa‐light‐chain‐enhancer of activated B cells signaling without increasing fibrogenic gene expression or cell proliferation. Conclusion: FGF15/19 does not act as a direct profibrotic mediator or mitogen to HSCs in our models, and the protection against fibrosis by FGF15 deficiency may be mediated through increased BA activation of FXR in HSCs.